Impact of health literacy and primary language on the decision to pursue trial of labor after prior cesarean delivery - Daisy Leon-Martinez; Christine Dehlendorf; Molly Zeme; W. John Boscardin; Anjali J. Kaimal; William A. Grobman; Miriam Kuppermann (BMC Pregnancy and Childbirth)
Abstract Background Both a trial of labor after cesarean (TOLAC) and elective repeat cesarean delivery (ERCD) are reasonable choices after a cesarean delivery, with differing risks and benefits. This study explores the impact of patient health literacy and primary language on the decision to pursue a TOLAC and on decision quality. Methods This is a secondary analysis of the Prior Cesarean Decision (PROCEED) trial, which examined the effect of a patient-centered decision support tool on rates of TOLAC and decision quality. Logistic regression was performed to estimate the association of limited health literacy (Newest Vital Sign score ≤4/6) and non-English primary language (NEPL) with TOLAC. Decision quality was assessed by calculating mean scores for decision-quality scales and using linear regression to estimate adjusted mean differences (aMD) by health literacy and NEPL. Results Among 1455 participants, 44.6% underwent TOLAC, and 71.0% of those with a TOLAC had a vaginal birth after cesarean (VBAC). Limited health literacy was associated with lower odds of TOLAC (aOR 0.60, 95% CI [0.38, 0.93]). For decision quality, limited health literacy was associated with similar scores for decisional conflict, shared decision-making, decision self-efficacy and decision satisfaction, but lower knowledge scores (3.9 vs. 5.4; aMD -0.7, 95% CI [-1.0, -0.5]). Compared to participants whose primary language was English (n=1043), those with NEPL (n=255) had similar odds of TOLAC (aOR 1.08, 95% CI [0.69, 1.68]), but greater decisional conflict (20.9 vs. 16.7; aMD 3.9, 95% CI [1.4, 6.3]) and lower decision self-efficacy (88.6 vs. 90.9; aMD -3.3, 95% CI [-5.6, -1.1]) and decision satisfaction (4.6 vs. 4.7; aMD −0.1, 95% CI [-0.2, 0.0]). Conclusions In this study of pregnant people with a prior cesarean and no prior VBAC, those with limited health literacy had lower odds of TOLAC and lower knowledge scores about risks and benefits of TOLAC vs. ERCD. While those with NEPL had similar odds of TOLAC, they had lower decision quality scores compared to those with those with English as a primary language. These findings indicate factors that may result in less effective counseling related to delivery options after prior cesarean and may contribute to differences in approach to delivery and decision quality.